2011
DOI: 10.1007/s00436-011-2546-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Clonorchis sinensis tetraspanin 2 extracellular loop 2

Abstract: In the course of examining EST of the liver fluke Clonorchis sinensis, a cDNA encoding the protein similar to tetraspanin 2 (TSP-2) of blood fluke schistosome was identified as CsTSP2. TSPs are a family of eukaryotic cell membrane-spanning proteins thought to anchor multiple proteins to one area of the cell membrane. Multiple sequence alignment of CsTSP2 revealed over 40% of identities with those of schistosomes. The CCC, PXSC, and CG motives characteristic to extracellular loop 2 (EC2) region of TSP-2 were we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…TSPs in trematodes have an important role in the development, maturation and stability of the tegument and are involved in the immune evasion of schistosomes [27,28]. Recently, many studies have focused on some members of the TSPs family as a vaccine candidate against schistosomiasis [20,28], alveolar echinococcosis [29,30], filariasis [31] and clonorchiasis [32].…”
Section: Introductionmentioning
confidence: 99%
“…TSPs in trematodes have an important role in the development, maturation and stability of the tegument and are involved in the immune evasion of schistosomes [27,28]. Recently, many studies have focused on some members of the TSPs family as a vaccine candidate against schistosomiasis [20,28], alveolar echinococcosis [29,30], filariasis [31] and clonorchiasis [32].…”
Section: Introductionmentioning
confidence: 99%
“…In parasites, recent studies show that tetraspanins are associated with the development, maturation and stability of the tegument of trematodes, and are involved in the immune evasion of schistosome [ 12 16 ]. Of note, some members of the tetraspanin family have been targeted as candidate vaccines against schistosomiasis [ 17 20 ], clonorchiasis [ 21 ], alveolar echinococcosis [ 22 25 ], and filariasis [ 26 ]. For example, inoculation with the LELs of two tetraspanins of S. mansoni (Sm-TSP-1 and Sm-TSP-2) was confirmed to significantly decrease the adult worm burdens and liver egg burdens in experimentally infected mice [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two tetraspanins (TSP1 and TSP2) were identified in the outer surface of S. mansoni and S. japonicum and function in tegument renewal ( Tran et al, 2010 ), and these have been found to be promising vaccine candidates to protect against schistosomiasis ( Tran et al, 2010 ; Chen et al, 2016 ). Tetraspanin 2 was previously found in C. sinensis ( Kim et al, 2011 ), but the function of tetraspanins in C. sinensis remains unknown. Annexin is another important protein identified in the C. sinensis tegument.…”
Section: Discussionmentioning
confidence: 99%